Development of agriculture in Ethiopia since the 1975 land reform - Belete, A.; Dillon, John L.; Anderson, F.M. (Wiley, 1991)
This paper mainly focusses 011 a macro review of the general course of Ethiopian agricultural development since the land reform of 1975. The food production has lagged behind the population growth - 3 percent population growth against 1.8 percent food production between 1970 and 1983. Recently the situation has, perhaps, further deteriorated. 71 percent of the total land mass is estimated to be suitable for agriculture, but only about 19 percent is cultivated. This suggests an underutilisation of land. Agricultural research and education which are essential to development have not been given due attention by the policy makers. As a result, the agricultural technologies used by farmers have changed little. Small-scale farmers have not been given the incentives necessary to expand production. Most of the credit, fertiliser and improved seeds go to state farms and producers' cooperatives. The favouring of large-scale and capital-intensive state-owned farming enterprises with credit, subsidies, and fiscal incentives, while neglecting smallholders, has contributed to the stagnation of agricultural production in Ethiopia. Overall, the analysis indicates that there has been no significant development of agriculture in Ethiopia following the 1975 land reform.